‘Disperse abroad in the land’: the role of wildlife in the dissemination of antimicrobial resistance - Arnold, Kathryn E.; Williams, Nicola J.; Bennett, Malcolm (Royal Society, 2016)
Antimicrobial resistance (AMR) has been detected in the microbiota of many wildlife species, including long-distance migrants. Inadequately treated wastes from humans and livestock dosed with antimicrobial drugs are often assumed to be the main sources ofAMR to wildlife. While wildlife populations closely associated with human populations are more likely to harbour clinicall important AMR related to that found in local humans and livestock, AMR is still common in remote wildlife populations with little direct human influence. Most reports of AMR in wildlife are survey based and/or small scale, so researchers can only speculate on possible sources and sinks of AMR or the impact of wildlife AMR on clinical resistance. This lack of quantitative data on the flow of AMR genes and AMR bacteria across the natural environment could reflect the numerous AMR sources and amplifiers in the populated world. Ecosystems with relatively simple and well-characterized potential inputs of AMRcan provide tractable, but realistic, systems for studying AMR in the natural environment. New tools, such as animal tracking technologies and high-throughput sequencing of resistance genes and mobilomes, should be integrated with existing methodologies to understand how wildlife maintains and disperses AMR.